Saving St Christopher: The History of a Looted Painting: In memory of David Scrase (1949–2020). Issue 3 (August 2021) - Schlenker, Ines
Abstract: When, the day after the Anschluss, the Viennese aristocrat Henriette von Motesiczky and her daughter, the painter Marie-Louise von Motesiczky, fled Vienna, they left behind an "old German" painting known as Knight and Devil. In 2016, by now identified as part of an early sixteenth-century altarpiece by the Master of St Christopher with the Devil and entitled St Christopher Meeting the Devil, the painting entered the collection of the Fitzwilliam Museum in Cambridge. It was donated by the Marie-Louise von Motesiczky Charitable Trust in memory of its former owner Karl von Motesiczky, Marie-Louise's brother, who had perished in Auschwitz. This article, based on detailed archival research, traces the history of St Christopher Meeting the Devil after 1938. The painting, forcefully taken from its owner, made its way through the National Socialist art-looting operation, encountering some of its main protagonists in the process. Sold at auction in 1943, it ended up at the Bayerische Staatsgemäldesammlungen in Munich from where, in 1950, it was restituted to the surviving members of the Motesiczky family, now living in England. In an exemplary way, the fate of St Christopher Meeting the Devil throws a light on the workings of the National Socialist looting system and the steps that the Allied Forces undertook after the war to rectify the crimes they uncovered. It also highlights the problems that gaps in the knowledge of an artwork's provenance can cause in the attempt to reconstruct cases of expropriation and emphasizes the role goodwill plays in reaching fair solutions.